ENCICLOPEDIA HISPANICA : MACROPEDIA (ENCYCLOPAEDIA BRITANNICA, 1989)
CONTENIDO: V. 1 AALTO, ALVAR, ARABIA. -- V. 2 ARABIA S.-BERNINI. -- V. 3 BERNOVLLI-CASA. -- V. 4 CASA BLANCA-CUY. -- V. 5 CHAC-ERATOST. -- V. 6 ERCILLA-GALICIA. -- V. 7 GALILEO-HISTOQUIM. -- V. 8 HISTORIA-KATMANDO. -- V. 9 KAWABATA-MECANICA. -- V. 10 MECANICA-NOVO. -- V. 11 NUBE-PLATON. -- V. 12 PLAUTO-ROMERO. -- V. 13 ROMMEL-TEOTIHUACAN. -- V. 14 TERAPEUTICA-ZWINGLI